Application of the Arabic Book in Your Hands in Learning Speaking Skills for Students in Higher Education - Hasbi, Muharam; Yani, Pobri Rizky (JURNAL IJ-ATL, 2024)
"Speech skill" Speech in the sense of a dialogue that occurs naturally between the members of the speaker and the speaker when communicating. This is the main tool for building mutual understanding and language is used as a medium. In the course of learning Arabic, students are given motivations to develop speech skills, i.e. skills to express desires, feelings and needs to others. This research aims to find out about the application of the book "Arabic in your hands" in learning the skill of speech. The participant of this research was a student in the program of the Department of Teaching Arabic at the Islamic State University of Hosmawi and using the Arabic book in your hands as an educational resource for speech skill. The research methodology used is qualitative, with data collected through observation, interview and documentation. The data is analyzed and concludes that this book helps students acquire Arabic speech skills and improve their vocabulary proficiency, as evidenced by the assessment results that showed an increase in students' vocabulary mastery.